EFEKTIVITAS PELAKSANAAN UNDANG-UNDANG NOMOR 2 TAHUN 1960 TENTANG PERJANJIAN BAGI HASIL TANAH PERTANIAN DI DESA UJUNG TERAN KECAMATAN SALAPIAN KABUPATEN LANGKAT - JULIA SARI (PREMISE LAW JURNAL, 2016)
The study used judicial emperical and descriptive method which was aimed to generally describe the condition of the implementation of law No. 2/1960 on Production Sharing Agreement on Farm Land at Ujung Teran Village, Salapian Subdistrict, Langkat Regency. The gathered data were analyzed by using judicial sociological method.The result of the study shows that the people at Ujung Teran Village do not know at all about the production sharing regulated in Law No. 2/1960. Therefore, they still comply with and use the adat ( traditional ) law which has developed from generation to generation. The infeasibility of Law No. 2/1960 is not because they are ignorant of the law or low quality of Law No. 2/1960, but because they really do not know about it. In order to uphold the implementation of Law No. 2/1960, it is recommended that the local Government widely inform Law No. 2/1960 to the people through the Village Head as the official which is close to his people. Keyword: Production Sharing Agreement